2007
DOI: 10.1016/j.compscitech.2007.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal behavior of non-crimp glass fiber reinforced layered clay/epoxy nanocomposites

Abstract: Mechanical and thermal properties of non-crimp glass fiber reinforced clay/epoxy nanocomposites were investigated. Clay/epoxy nanocomposite systems were prepared to use as the matrix material for composite laminates. X-ray diffraction results obtained from natural and modified clays indicated that intergallery spacing of the layered clay increases with surface treatment. Tensile tests indicated that clay loading has minor effect on the tensile properties. Flexural properties of laminates were improved by clay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
104
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 15 publications
7
104
0
1
Order By: Relevance
“…However, the nanoclay incorporated composites showed significant improvements in the mechanical properties with respect to those without nanoclay. This is due to the greater adhesion between the matrix and the filler at the interface of the nanocomposite [38]. That is also evident from the FTIR and SEM study.…”
Section: Tensile Propertiessupporting
confidence: 54%
“…However, the nanoclay incorporated composites showed significant improvements in the mechanical properties with respect to those without nanoclay. This is due to the greater adhesion between the matrix and the filler at the interface of the nanocomposite [38]. That is also evident from the FTIR and SEM study.…”
Section: Tensile Propertiessupporting
confidence: 54%
“…Both flexural strength and interlaminar toughness has been improved. Bozkurt et al [24] found MMT clay can significant increase flame resistance of glass fiber reinforced epoxy. Kornmann et al [25] produced glass fiber reinforced laminates with a matrix of layered clay/epoxy system and showed that flexural strength of the composites is increased due to the presence of the nano particles in the matrix.…”
Section: Introductionmentioning
confidence: 98%
“…However most of these developments result in compromising the in-plane mechanical properties; where stitching, braiding, 3D weaving, and z-pinning reduce the overall in-plane properties, toughened resins and interleaving can degrade the compressive strength of the composite if not incorporated thoughtfully. Micro-and nanosized fillers are also used to improve interlaminar properties [15][16][17]. A limitation of these additives is the formation of large stress concentrations around agglomerated fillers.…”
Section: Introductionmentioning
confidence: 99%